Alcohol consumption and violence among Argentine adolescents - Mariaelena Pierobon; Mariam Barak; Sahel Hazrati; Kathryn H. Jacobsen (Jornal de Pediatria (Versão em Português), 2013)
Objective: This study investigated the association between alcohol and violence among Argentine youth. Methods: Data from the 2007 Argentina Global School-based Student Health Survey (GSHS), a nationally representative survey of middle school students, were examined using age-adjusted logistic regression models. Results: Of the 1,328 participating students aged 13 to 15 years old, 51.9% reported drinking alcohol in the previous month, with higher rates among males (p = 0.04) and older students (p < 0.01). Both male and female drinkers were nearly twice as likely as non-drinkers to report being physically attacked, being in a physical fight, and having thoughts about self-directed violence. Among drinkers, those who reported poor mental health, were victims of bullying, used tobacco or drugs, or skipped school without per- mission were approximately twice as likely as other drinkers to have engaged in violent activities. Conclusion: Public health interventions targeting violence among young adolescents should be developed in combination with alcohol education programs.